Perbandingan Efektifitas Ekstrak Daun Kelor (Moringa oleifera L.) dan Buah Bit (Beta vulgaris L.) Dalam Meningkatkan Kadar Hemoglobin (Hb) Pada Remaja Putri dengan Anemia: Comparison of the Effectiveness of Moringa Leaf Extract (Moringa oleifera L.) and Bit Fruit (Beta vulgaris L.) in Increasing Hemoglobin (Hb) Levels in Adolescent Girls with Anemia - Isy Royhanaty; Yuli Yuli; Novi Anding Suciati (Journal of Health, 2023)
Girls are high risk of suffering from anemia, because there is an increase in iron needs due to growth and menstruation. The normal hemoglobin levels for girls is 12 g/dl. Natural supplementation that has an anti-anemia effect, namely Moringa Leaf (Moringa oleifera L.) and Bit Fruit (Beta vulgaris L.). Research Objectives is to determine the difference in the effectiveness of Moringa leaf extract and beet fruit extract on increasing Hb levels in girls at SMK Muhammadiyah I Pemalang. The research is Quasi Experiment, with a two group pre-test-post-test design.  Group 1 was given 500 mg of Moringa leaf extract which was consumed 2 times a day for 7 days. Group 2 was given 1000 mg of beetroot extract which was consumed 2 times a day for 7 days. The sampling technique used purposive sampling. The sample criteria being teenager aged 12-18 years, menstruating, not allergic to moringa leaf extract and beetroot extract, and not menstruating during the intervention period. Results: Moringa leaf extract (mean rank 27,50) was more effective than beet fruit extract (mean rank 9,50) in increasing Hb levels. Mann_Whitney U test obtained p value 0.000 < 0.05, which means that there is a significant difference in effectiveness between Moringa leaf extract and beet fruit extract on increasing Hb levels in adolescent girls at SMK Muhammadiyah I Pemalang. Moringa leaf extract is more effective than beet fruit extract in increasing Hb levels. Moringa leaf extract and beet fruit extract can be used as non-pharmacological therapy in increasing hemoglobin level.